2003
DOI: 10.1074/jbc.m301468200
|View full text |Cite
|
Sign up to set email alerts
|

Broadly Distributed Chemical Reactivity of Natural Antibodies Expressed in Coordination with Specific Antigen Binding Activity

Abstract: Antibody (Ab) nucleophilic reactivity was studied using hapten and polypeptide antigens containing biotinylated phosphonate diester groups (covalently reactive antigen analogs, CRAs). Polyclonal IgG from healthy donors formed covalent adducts with a positively charged hapten CRA at levels superior to trypsin. Each of the 16 single chain Fv clones studied expressed a similar reactivity, indicating the V domain location of the nucleophiles and their broad distribution in diverse Abs. The formation of hapten CRA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(72 citation statements)
references
References 43 publications
3
67
1
1
Order By: Relevance
“…the activation of Ser/Thr side chain hydroxyl groups by hydrogen bonding to His residues, and can be detected by covalent binding to electrophilic phosphonate diesters (9,10). Using these compounds as covalently reactive analogs of antigens (CRAs), we observed that IgG Abs express nucleophilic reactivities comparable to trypsin (11). Despite their nucleophilic competence, IgG Abs display low efficiency proteolysis, presumably due to deficiencies in steps occurring after formation of the acyl-Ab intermediate, viz., water attack on the intermediate and product release.…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…the activation of Ser/Thr side chain hydroxyl groups by hydrogen bonding to His residues, and can be detected by covalent binding to electrophilic phosphonate diesters (9,10). Using these compounds as covalently reactive analogs of antigens (CRAs), we observed that IgG Abs express nucleophilic reactivities comparable to trypsin (11). Despite their nucleophilic competence, IgG Abs display low efficiency proteolysis, presumably due to deficiencies in steps occurring after formation of the acyl-Ab intermediate, viz., water attack on the intermediate and product release.…”
mentioning
confidence: 94%
“…Splenocyte-CRA Binding-Synthesis of compounds I-IV and confirmation of their chemical identity have been published (11,18). Compounds I, III, and IV are diphenyl phosphonate esters reactive with nucleophilic sites (9,10,18).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations